KAJIAN PENGARUH PEMBANGUNAN JALAN TOL SEMARANG - DEMAK TERHADAP KINERJA JALAN RAYA KALIGAWE - Rachmat Mudiyono; Gata Dian Asfari (Universitas Islam Sultan Agung Semarang, 2021)
The increasing movement causes traffic jams. One of the congestion occurred on Jalan Raya Kaligawe, Semarang. Jalan Raya Kaligawe is a road located close to the coast. So that when the sea water experiences high tide, the road will be inundated by tidal floods. This condition results in very high traffic jams every year. To deal with congestion and overcome the problem of sea water flooding, the government plans to build the Semarang - Demak Toll Road. With the existence of this Toll Road, it is hoped that congestion on the Kaligawe Road will be reduced. But the reduction in congestion needs research. So the researchers conducted a study on the effect of the construction of the Semarang - Demak Toll Road on the performance of the Kaligawe Highway. The purpose of this study, among others, is to determine the level of service, prediction of the diversion of traffic loads and predictions of increasing work on Jalan Raya Kaligawe. This study uses three stages in the research method, namely the identification stage, the data collection and processing stage, and the analysis and conclusion stages. The analysis technique used in this research is the formulation of traffic loading around the location due to development, both at the time and post, added with base traffic to get a real loading on the area of influence with the construction of the Semarang - Demak toll road.